Comparative Assessment of Methods for Estimating Biomass in Forest Ecosystem - Negi, J. D. S.; Sharma, S. C.; Sharma, D. C. (Indian Forester, 1988)
The paper describes various methods of biomass estimation in forest ecosystems with their limitations and applicability. Some comparisons have also been made between the conventional stratified tree techniques and other methods and the regression technique has been found to be satisfactory for wider application or where the destructive sampling is not desirable.